2020
DOI: 10.1155/2020/6458425
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance for Social Health Insurance among Health Professionals in Government Hospitals, Mekelle City, North Ethiopia

Abstract: Background. Ethiopia is one of the countries with high out-of-pocket payments leading to catastrophic health expenditure. The government of Ethiopia introduced social health insurance (SHI) scheme with the overall objective of achieving universal health care access. Studying health professionals’ acceptance to pay for social health insurance is crucial for the successful implementation of the scheme. Therefore, this study aimed to assess the acceptance of social health insurance and its associated factors amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
3
18
2
Order By: Relevance
“…Furthermore, those who had no history of difficulty covering their medical bill were less likely willing to pay for SHI. This is consistent with a study revealed from the northern part of Ethiopia, Mekelle city [ 28 ], and southern Ethiopia, Wolaita Sodo town [ 18 ], Sierra Leone [ 27 ]. This might be due to that individuals who were unable to cover their medical bill may need risk-sharing nature of the insurance [ 29 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, those who had no history of difficulty covering their medical bill were less likely willing to pay for SHI. This is consistent with a study revealed from the northern part of Ethiopia, Mekelle city [ 28 ], and southern Ethiopia, Wolaita Sodo town [ 18 ], Sierra Leone [ 27 ]. This might be due to that individuals who were unable to cover their medical bill may need risk-sharing nature of the insurance [ 29 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…This could be due to that there was no health insurance scheme (SHI or CBHI) in the town before and knowing about the benefits of health insurance is important to be willing to pay. This might be also due to having good awareness about health insurance and trust in a health insurance agency [ 22 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not matched what the government needs according to the newly proposed SHI scheme which needs more effort to resolve the factors affecting acceptance and promote the benefit of the insurance. Indeed, the acceptance level of SHI in other sectors like that of healthcare is higher which indicates a growing interest of participation [42].…”
Section: Discussionmentioning
confidence: 99%
“…A self-administered questionnaire was used to collect data, which was prepared based on previous literatures and adjusted as needed ( 15 , 18 23 ). It was divided into five sections: sociodemographic factors, SHI knowledge, SHI perception, health and health-related issues, and WTP (readiness to pay) for SHI.…”
Section: Methodsmentioning
confidence: 99%